Understanding soil health - Johnson, Karen; Kihara, Job; Fan, Mingsheng; Congreves, Kate A.; González-Pérez, José A.; Deb, Shovik; de Vries, Franciska (Elsevier, 2024)
Soil is a crucial ecosystem that underpins the survival of plants, animals, and humans. While climate change is expected to significantly impact soil communities, geochemical cycling, and nutrient availability, there remains a lack of consensus on the precise nature of these effects. A fundamental and pressing question concerns the definition of soil health regarding what properties constitute healthy soil. This Voices asks: what property must be urgently consolidated into the soil health framework to support broader sustainability?